High-density seismic network for monitoring Alentejo region (Portugal) and Mitidja basin region (Algeria) - Manso, Marco (2020)
The seismic sensor network Alentejo (SSN-Alentejo) brings a new approach in seismological survey based on networked low- cost sensors and acquisition systems. It is developed by the Earth Sciences Institute (Instituto de Ciências da Terra, University of Evora) to bring the most dense seismic sensor network ever deployed in Portugal. By combining high-sensitive sensors with low- cost sensors, this novel network aims to improve the characterisation of seismic activity in the region, by augmenting existing sensing and monitoring capabilities, enabling the opportunity to observe, for the first time in Portuguese territory, real-time monitoring of the seismic activity in high resolution. In this study, we start by describing the seismicity along the occidental border between the Eurasian-Nubian plates, including the two regions of our interest: the Arraiolos region, in Portugal, and the Mitidja basin, in Algeria. We then present our work in designing and implementing a high-density sensor network, including low-cost sensor systems and server platforms. The conducted tests have proven the feasibility of the overall platform, including its detectability capability. Future work includes the deployment of the sensor network in the Alentejo region. Since seismogenic zones such as the Mitidja or Chelif basins in Algeria will also benefit from having a high-density network, we will also seek collaboration with Algerian institutions.